Pengaruh Tekanan Hidrostatis Terhadap Debit Rembesan Sekat Kanal Berkonstruksi Beton pada Lahan Gambut - Risterianto As Nyagin; Haiki Mart Yupi; Dwi Anung Nindito (Jurnal Basement : Jurnal Teknik Sipil, 2023)
Peat soil has a wet and soft texture. Degraded peatlands due to reduced water content will cause drought andhave the potential for fires. One way to overcome the drought is by wetting the peat, namely by building canalblocks. This study aims to determine the effect of different hydrostatic pressure height on seepage discharge.The methods used are documentation, observation, and quantitative data analysis. This research is located inthe city of Palangka Raya carried out from April 10 – May 7 2022. The data analysis technique used is theanalysis of the coefficient of determination on the graph of the effect of the hydrostatic pressure difference onseepage discharge. The initial stage of this research was to collect the data needed to design a concreteconstructed canal blocking prototype. The building is scaled from prototype to distortion model where the scale used is 1:10 on the vertical and 1:25 on the horizontal. In testing the physical model of canal blocking, the test time for observing seepage that occurs in the flume is carried out within 240 minutes where observations are made 30 minutes for each seepage. In the final stage, a model test was carried out with variations in the water level at the upstream being 30 cm and at the downstream the water was empty, without any flow velocity. Based on the results of the model test, it shows that the smaller the hydrostatic pressure difference (ΔTTH) the smaller the seepage discharge value. The results of the largest and smallest seepage discharges in this study were 45 cm3/s at 100% ΔTTH and 11,9 cm3/s at 46% ΔTTH.